Adaptation and early implementation of the PREdiction model for gene mutations (PREMM5™) for lynch syndrome risk assessment in a diverse population - Kathleen F. Mittendorf; Chinedu Ukaegbu; Marian J. Gilmore; Nangel M. Lindberg; Tia L. Kauffman; Donna J. Eubanks; Elizabeth Shuster; Jake Allen; Carmit McMullen; Heather Spencer Feigelson; Katherine P. Anderson; Michael C. Leo; et al. (Familial Cancer, 2022)
Lynch syndrome (LS) is the most common inherited cause of colorectal and endometrial cancers. Identifying individuals at risk for LS without personal cancer history requires detailed collection and assessment of family health history. However, barriers exist to family health history collection, especially in historically underserved populations. To improve LS risk assessment in historically underserved populations, we adapted the provider-facing PREdiction Model for gene Mutations (PREMM 5 ™ model), a validated LS risk assessment model, into a patient-facing electronic application through an iterative development process involving expert and patient stakeholders. We report on preliminary findings based on the first 500 individuals exposed to the adapted application in a primary care population enriched for low-literacy and low-resource patients. Major adaptations to the PREMM 5 ™ provider module included reduction in reading level, addition of interactive literacy aids, incorporation of family history assessment for both maternal and paternal sides of the family, and inclusion of questions about individual relatives or small groups of relatives to reduce cognitive burden. In the first 500 individuals, 90% completed the PREMM 5 ™ independently; of those, 94% did so in 5 min or less (ranged from 0.2 to 48.8 min). The patient-facing application was able to accurately classify 84% of patients as having clinically significant or not clinically significant LS risk. Our preliminary results suggest that in this diverse study population, most participants were able to rapidly, accurately, and independently complete an interactive application collecting family health history assessment that accurately assessed for Lynch syndrome risk.

Implementation of a Systematic Tumor Screening Program for Lynch Syndrome in an Integrated Health Care Setting - Elizabeth V. Clarke; Kristin R. Muessig; Jamilyn Zepp; Jessica E. Hunter; Sapna Syngal; Louise S. Acheson; Georgia L. Wiesner; Susan K. Peterson; Kellene M. Bergen; Elizabeth Shuster; James V. Davis; Jennifer L. Schneider; et al. (Familial Cancer, 2019)